Applications of mechanism design in market-based demand-side management: A review - Khaled Abedrabboh (10063125) (2023)
The intermittent nature of renewable energy resources creates extra challenges for the operation and control of the electricity grid. Demand flexibility markets can help in dealing with these challenges by introducing incentives for customers to modify their demand. Market-based demand-side management (DSM) have garnered serious attention lately due to its promising capability of maintaining the balance between supply and demand, while also taking customers’ preferences into consideration. Many researchers have proposed using concepts from mechanism design theory in their approaches to market-based DSM. In this work, we provide a review of the advances in market-based DSM using mechanism design. We provide a categorisation of the reviewed literature and evaluate the strengths and weaknesses of each design criteria. We also study the utility function formulations used in the reviewed literature and provide a critique of the proposed indirect mechanisms. We show that despite the extensiveness of the literature on this subject, there remains concerns and challenges that should be addressed for the realistic implementation of such DSM approaches. These include privacy concerns, market efficiency, scalability, convergence speed, and modelling the intertemporal dependence of electricity consumption. We draw conclusions from our review and discuss possible future research directions. Other Information Published in: Renewable and Sustainable Energy Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rser.2022.113016